The Effect of Al-Qur'an Murottal Therapy Surah Ar-Rahman on Reducing Blood Pressure in Menopausal Women Suffering from Hypertension in Purwakarta Regency, Indonesia (Journal of Anesthesiology and Clinical Research, 2024)
Background: Hypertension is a chronic disease that often occurs in menopausal women. Murottal therapy from Al-Qur'an Surah Ar-Rahman is believed to lower blood pressure. This study aims to determine the effectiveness of murottal therapy from Al-Qur'an Surah Ar-Rahman on reducing blood pressure in menopausal women with hypertension in Purwakarta Regency, Indonesia.Methods: This research used a quasi-experimental design with a pretest-posttest with a control group design. A total of 60 menopausal women with hypertension in Purwakarta Regency were randomly divided into two groups: the intervention group (n=30) who received murottal therapy of Al-Qur'an Surah Ar-Rahman for 30 minutes every day and the control group (n=30) who did not receive the intervention. Blood pressure was measured before and after intervention for 4 weeks.Results: The results showed that there was a significant difference in the reduction in systolic and diastolic blood pressure between the intervention and control groups after 4 weeks (p
Keywords: Blood pressure; Hypertension; Menopausal women; Murottal Al-Qur'an; Surah Ar-Rahman